Researching Roma Ethnic Group from Economic Perspective : Discrimination, Experimental Research and Missing Data - Bajzíková, Stanislava; Čermáková, Klára; Pavelka, Tomáš, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This dissertation investigates stereotypes and discrimination against the Roma minority in the Czech Republic and Slovakia, using experimental and empirical methods. A novel measure, based on a multiple-price list—a method commonly employed in experimental economics—was introduced to assess stereotypes related to work attitudes. The study involved 100 students from the majority population who completed tasks individually and in teams, with the option to choose between Roma or non-Roma teammates. Results revealed that Roma individuals were expected to produce lower outputs, with these expectations primarily influenced by personal experiences rather than by broader social or risk preferences. In addition to experimental data, this research utilized a 2014 Ipsos survey to explore how financial, physical, welfare, and wealth insecurities affect perceptions of Roma individuals. Analysis, controlling for demographic factors such as age, education, income, and number of children, found that financial insecurity correlated with less favorable attitudes toward Roma neighbors, while physical insecurity correlated with a greater willingness to accept Roma as neighbors. Intolerance toward Roma was found to decrease with age, while income, education, and regional factors had minimal impact. The dissertation also addresses the critical issue of acquiring ethnic data within the Roma community, emphasizing the importance of such data for understanding marginalized groups and informing inclusive policies. It discusses the legal, ethical, and practical challenges in collecting this data, including privacy concerns, consent, and historical mistrust. Despite these challenges, the necessity of ethical data collection practices to advance equity, inclusivity, and social justice is underscored.
Overall, this study provides valuable insights into minority-majority relations, highlighting the need for societal cohesion and mutual understanding to overcome stereotypes and promote a more inclusive society.
Vedoucí práce: Klára Čermáková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations